La gamificación como estrategia didáctica para el desarrollo de la habilidad de escritura en estudiantes de bachillerato en la unidad educativa fluminense del cantón Buena Fe, periodo lectivo 2023- 2024 - Pineda Burgos, María Fernanda (2024)
Writing still constitutes a challenge for teaching and learning despite its importance in human communication. The objective of this research is to design a system of activities with the use of gamification for the development of writing skills in third- year high school students in the Language and Literature subject of the Fluminense Educational Unit located in the Los Ríos Province. The research to be developed has a mixed approach, with applied, correlational and field research. Theoretical methods are used to study the decisive variables in the research and empirical methods associated with the diagnosis made, including observation, documentary review and interviews. It was necessary to test the reliability and validity of the instrument. A system of activities is designed for the development of writing skills with the use of gamification, for which four stages or components consistent with the development of the skill are established: motivation, development, evaluation - monitoring and reinforcement for which they are created. a group of actions centered on the student. The effectiveness of the proposal made is verified according to the perception of a group of experts from the institution through the application of the Net Promoter Index with a result of 72.5, greater than 50 percentage units, which is why the proposal is considered excellent